The relative performance of socially responsible investment funds: New evidence from Austria - Sebastian Rathner (University of Salzburg, Department of Social Sciences and Economics, 2013)
The aim of this paper is to compare the financial performance of Austrian SRI funds to the performance of Austrian conventional funds. 43 SRI and 1395 conventional funds are found for the analysis. Jensen's alpha and Carhart's 4-factor alpha are used to evaluate fund performance. The results suggest that throughout the sample period from 02/1992 to 3/2012 there was not any performance difference between the two types of funds. However, more detailed results show that SRI equity (debt) funds significantly outperform (underperform) their conventional peers. SRI funds significantly outperform (underperform) conventional funds in the second (first) half of the sample period. Furthermore, signing up to the European SRI Transparency Code (as a proxy for SRI quality) as well as using a matching procedure influence the observed results.
Keywords: G12; M14; 330; Ethical investment; Investment fund performance; Socially Responsible Investment (SRI); Sustainability